Conhecimento e educação na pós-modernidade - OLIVEIRA, Cássia Araújo de (Universidade Federal do Pará, 2020)
This article has as main objective to demonstrate the influence of the idea of after-modernity for the knowledge and, therefore for the education. After-modernity in the sphere of the knowledge and the education possess a criticalreflexive dimension, mainly because the expression after-modernity problematizes the modern and if makes gift in many situations as rupture of proper modernity. The proposal of the article is the critical one that the after-modernity idea offers as production of knowledge in education, in the measure where the effect of aftermodernity appear as it has detached in the current debate of knowledge in education. For the methodology of the article it was used of bibliographical research based at. Gallo (2006), Pagni (2006), Habermas (2000).The article searches to understand where sensible the education if inserts in the after-modernity idea.